The Review of National Defense Budget Policy to the Indonesian Economy - Kennedy, Posma Sariguna Johnson; L.Tobing, Suzanna Josephine; Lumbantoruan, Rutman (Universitas Kristen Indonesia, 2017)
In building the power of the nation, there are two main factors that must be considered, namely economic and defense factors. The ups and downs of the defense budget generally have an impact on the national economy, while the economy and defense are the main components in building the strength of a nation. The general objective from this research is to look at the picture of the effect of the threat level of Indonesia's strategic environment on defense budget policy and its effect on the national economy. From the study show that the effect of the defense budget on the economy is still very small. But indirectly, it can still keep the demand and production process, and eliminate potential threats to disturbances on aggregate demand and supply, although the potential threat from the strategic environment shows an upward trend. Increased defense budgets do not lead to a reduction in other welfare budgets such as the education budget. However, increased threats must be considered because the education process can be disrupted. Therefore, the determination of defense budget, education budget, and other welfare budget must be taken into account in a balanced manner so as to give effect of low cost opportunity. Keywords: economy, defense, defense budget policy.